MR Imaging in Wegener Granulomatosis of the Spinal Cord - Mentzel, Hans-J.; Neumann, Thomas; Fitzek, Clemens; Sauner, Dieter; Reichenbach, Jürgen R.; Kaiser, Werner A. (American Journal of Neuroradiology, 2003)
Summary: Wegener granulomatosis is a multisystemic disorder characterized by necrotizing vasculitis that primarily involves the respiratory tract. The orbits, heart, skin, joints, and nervous system are frequently involved. We describe the MR imaging findings of Wegener granulomatosis in the cervical spine and correlate them with the histopathologic features. MR imaging showed epidural liquid masses surrounded by granulomatous masses that compressed the cervical myelin from behind.